Advances in Surgical Approaches to Dural Fistulas. (1st February 2014) - Youssef, Patrick P.; Schuette, Albert Jess; Cawley, C. Michael; Barrow, Daniel L.
Abstract: Dural arteriovenous fistulas are abnormal connections of dural arteries to dural veins or venous sinuses originating from within the dural leaflets. They are usually located near or within the wall of a dural venous sinus that is frequently obstructed or stenosed. The dural fistula sac is contained within the dural leaflets, and drainage can be via a dural sinus or retrograde through cortical veins (leptomeningeal drainage). Dural arteriovenous fistulas can occur at any dural sinus but are found most frequently at the cavernous or transverse sinus. Leptomeningeal venous drainage can lead to venous hypertension and intracranial hemorrhage. The various treatment options include transarterial and transvenous embolization, stereotactic radiosurgery, and open surgery. Although many of the advances in dural arteriovenous fistula treatment have occurred in the endovascular arena, open microsurgical advances in the past decade have primarily been in the tools available to the surgeon. Improvements in microsurgical and skull base approaches have allowed surgeons to approach and obliterate fistulas with little or no retraction of the brain. Image-guided systems have also allowed better localization and more efficient approaches. A better understanding of the need to simply obliterate the venous drainage at the site of the fistula has eliminated the riskier resections of the past. Finally, the use of intraoperative angiography or indocyanine green videoangiography confirms the complete disconnection of fistula while the patient is still on the operating room table, preventing reoperation for residual fistulas.